2023
DOI: 10.3390/ijms24043816
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Alleviates Chromium Toxicity in Maize by Modulation of Cell Wall Polysaccharides Biosynthesis, Glutathione Metabolism, and Antioxidant Capacity

Abstract: Melatonin, a pleiotropic regulatory molecule, is involved in the defense against heavy metal stress. Here, we used a combined transcriptomic and physiological approach to investigate the underlying mechanism of melatonin in mitigating chromium (Cr) toxicity in Zea mays L. Maize plants were treated with either melatonin (10, 25, 50 and 100 μM) or water and exposed to 100 μM K2Cr2O7 for seven days. We showed that melatonin treatment significantly decreased the Cr content in leaves. However, the Cr content in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 92 publications
1
7
0
Order By: Relevance
“…Furthermore, the supplementation in maize plants resulted in a higher photosynthetic rate, increases in chlorophyll content, and improvement in antioxidant enzyme synthesis, effectively mitigating Cr toxicity. The research also explored the role of melatonin in regulating the heavy metal binding ability of the cell wall, further contributing to enhanced stress tolerance [ 107 ].…”
Section: Melatonin and Its Protective Effects On Photosynthetic Machi...mentioning
confidence: 99%
“…Furthermore, the supplementation in maize plants resulted in a higher photosynthetic rate, increases in chlorophyll content, and improvement in antioxidant enzyme synthesis, effectively mitigating Cr toxicity. The research also explored the role of melatonin in regulating the heavy metal binding ability of the cell wall, further contributing to enhanced stress tolerance [ 107 ].…”
Section: Melatonin and Its Protective Effects On Photosynthetic Machi...mentioning
confidence: 99%
“…Melatonin, an endogenous molecule with high conservation across eukaryotic evolution, plays a pivotal role as a signaling molecule in various biological processes and responses to abiotic stress in plants. These stresses include salt stress [33,34], drought stress [47], and heavy metal stress in certain species [35][36][37]. Recent studies have also revealed that melatonin mitigates Al toxicity in soybean [38], wheat [39], and maize [40,41] through diverse mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most extensively characterized and studied roles of melatonin is its ability to enhance plant tolerance to various abiotic stresses. For instance, exogenous melatonin has been shown to improve salt tolerance in sunflower [33] and rice [34], it plays a crucial role in mitigating the toxicity of heavy metals, and it alleviates cadmium toxicity in Chinese cabbage seedlings [35], chromium toxicity in maize [36], and copper toxicity in cucumber [37]. Researchers have also explored the potential alleviating effects of melatonin on Al toxicity.…”
Section: Of 17mentioning
confidence: 99%
See 1 more Smart Citation
“…According to the transcriptomic and proteomic data, this study found that exogenous MT increased the GSH content and GR activity in hairy roots (Figure 5). It has been shown that using melatonin to alleviate cadmium stress in maize increased GSH content [35], while the use of melatonin alleviated Cd stress and enhanced GR activity [36]. Wang et al (2012) found that melatonin increased the concentration of GSH by stimulating the activity of γ-glutamylcysteine synthetase, thereby delaying the senescence of apple leaves [37].…”
Section: Discussionmentioning
confidence: 99%